Critical factors to be considered when testing nanomaterials for genotoxicity with the comet assay. (19th December 2014) - Huk, Anna; Collins, Andrew R.; El Yamani, Naouale; Porredon, Constanca; Azqueta, Amaya; de Lapuente, Joaquín; Dusinska, Maria
Abstract : The comet assay is widely used to test the genotoxicity of engineered nanomaterials (ENMs) but outcomes may vary when results from different laboratories, or even within one laboratory, are compared. We address some basic methodological considerations, such as the importance of carrying out physico-chemical characterisation of the ENMs in test-medium, performing uptake and cytotoxicity tests, and testing several genotoxicity-related endpoints. In this commentary, we discuss the different ways in which concentration of ENMs can be expressed, and stress the need to include appropriate controls and reference standards to monitor variation and avoid interference. Treatment conditions, including cell number, cell culture plate format and volume of treatment medium on the plate are crucial factors that may impact on results and thus should be kept constant within the study.